Process intensification of hydrogen production by steam reforming of methane over structured channel packing catalysts - Kuang Xiao-Gang; Zhang Li; Ren Yan-Lun; Wang Xing-Wei (E3S Web of Conferences, 2023)
The industrial methane steam reforming reaction usually employs particulate catalyst that are easy to prepare and cost-effective, but suffer from problems such as high reactor pressure drop and low overall catalyst utilization. In this study, the Ni-Al2CaO4 powder prepared by the equal volume impregnation method was subjected to particle size control using a pressing method, and was made into catalyst particles of different sizes. Some of the catalysts were filled into honeycomb structures with cordierite and metal substrates, respectively, to prepare regular channel packing catalysts. The differences in methane steam reforming conversion rate, H2/CO selectivity, and overall pressure drop among the three catalysts were compared, and the influence of particle size and regular channel on reaction performance was systematically explored. The results showed that under the same conditions, as the catalyst particle size increased, the methane conversion rate and pressure drop increased. The regular channel packing catalysts with the two substrates showed similar pressure drop levels, but the metal substrate exhibited a higher methane conversion rate due to its excellent thermal conductivity. Compared with single-particle catalysts of the same size, the pressure drop of the metal substrate regular channel packing catalysts was reduced by more than 25%. Under the conditions of a gas hourly space velocity of 2000 h-1, a reaction temperature of 700 °C, and a water-to-carbon ratio of 3, the 40-60 mesh metal substrate regular packing catalysts showed a 7% increase in methane conversion rate, reaching 95.2%.